Eksplorasi Guru Pendidikan Agama Islam dalam Menanamkan Karakter Islami di SMP Muhammadiyah 4 Surabaya - Amani, Alika Atha; Amalia, Saniyah Rizky; Sari, Venika Devita (Lembaga Yasin AlSys, 2023)
This writing is presenting about the Pendidikan Agama Islam (PAI) class for the pupils. One of the most crucial pillars of character education is Pendidikan Agama Islam (PAI). The development of students' religious sense will be the foundation for a strong character education program; as a result, the PAI lesson serves as a supporting lesson for character education. Through the teaching and learning of PAI, students are taught the importance of believing in God as the cornerstone of their faith, the quran and hadith as their way of life, fiqh as a code of law when studying Islam, the history of Islam as a moral example, and ethics as the standard of human behavior.